A study on the effects of customer value and perceived value on customer satisfaction, brand loyalty and pepurchase intention - Dehghan, Nabi Allah; Alizadeh, Hamid; Mirzaei-Alamouti, Sedighe (Serbian Journal of Management, 2015)
Abstract Today, more than ever we see an increase in the importance of customer-orientation, and it’s consideration as an important competitive advantage of organizations and its role in business success and development. The aim of this study is to survey a development of customer-oriented culture in chain stores, and also to discuss the relationships between the dimensions of customer value, perceived value, customer satisfaction, brand loyalty and repurchase intention. This study is based on a survey research, and the statistical population is consisted of customers of Shahrvand chain stores in Tehran, and the selected samples are 390 persons from those customers. The data collection tool was a questionnaire and Confirmatory factor analysis and structural equation modeling techniques have been used to analyze the collected data. The results show that in Shahrvand chain stores, customer value affects on the Customer satisfaction. Moreover, it shows that customer satisfaction also affects brand loyalty. And at last it reveals that the proposed model explains the relationships between aspects of customer value, perceived value, customer satisfaction, brand loyalty and repurchase intention in an effective way.